KOMPETISI, KOMPROMI DAN COALITION AGREEMENT: BEREBUT KURSI WAKIL GUBERNUR DKI JAKARTA DI TENGAH KONTESTASI PEMILIHAN PRESIDEN 2019 - Mahpudin, Mahpudin; Lestari, Fransisca Mega (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2021)
Competition and compromise in party coalitions is a necessity. This happens because parties have different agendas, interests, and political goals. The party's choice to compete or compromise is highly dependent on the political situation and interests that are being faced. The implication is that the choice can be single, namely choosing one (competition or compromise with other parties), or both go hand in hand. Therefore, parties often make political contracts in the form of coalition agreements to ensure that the coalitions that are built provide political benefits. This article attempts to portray competition and compromise within the coalition party between Gerindra and PKS. The results of the study show that Gerindra and PKS must reconcile the two logics. On the one hand, these two parties must show unity during the 2019 presidential election for the succession of the Prabowo-Sandiaga Uno candidacy. However, at the same time they are competing in the context of filling the position of deputy governor. The two competing logics caused the coalition parties to compete and at the same time compromise. The choice to compete and compromise has implications for the presence of a coalition agreement among coalition parties. However, the coalition agreement is not oriented to policy issues, but rather is based on the interests of power. The implication is that the coalition agreement becomes the glue as well as the destroyer of the party coalition building.